2012
DOI: 10.1093/pcp/pcs113
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of CEBiP and CERK1 Homologs in Arabidopsis and Rice Reveals the Presence of Different Chitin Receptor Systems in Plants

Abstract: Chitin is a representative microbe-associated molecular pattern (MAMP) molecule for various fungi and induces immune responses in many plant species. It has been clarified that the chitin signaling in rice requires a receptor kinase OsCERK1 and a receptor-like protein (Os)CEBiP, which specifically binds chitin oligosaccharides. On the other hand, Arabidopsis requires a receptor kinase (At)CERK1 for chitin signaling but it is not clear whether the plant also requires a CEBiP-like molecule for chitin perception/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
168
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(174 citation statements)
references
References 38 publications
3
168
0
3
Order By: Relevance
“…2). These results support previous work that demonstrated that chitin-triggered, CERK1-dependent increases in gene expression are normal in a lym1,2,3 triple knockout (11). Chitin-induced PD flux reduction occurs in cerk1-2 mutant plants, indicating that as LYM2 is not required for CERK1-mediated responses, neither is CERK1 required for LYM2-mediated responses (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…2). These results support previous work that demonstrated that chitin-triggered, CERK1-dependent increases in gene expression are normal in a lym1,2,3 triple knockout (11). Chitin-induced PD flux reduction occurs in cerk1-2 mutant plants, indicating that as LYM2 is not required for CERK1-mediated responses, neither is CERK1 required for LYM2-mediated responses (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…In rice, chitin perception employs the receptor-like protein CEBiP, but a similar function for its Arabidopsis homolog, LYM2, has been elusive despite evidence that LYM2 is a chitin-binding protein (7,11). This study has identified that LYM2 has a specific role that mediates a reduction in molecular flux through PD in the presence of chitin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Arabidopsis, CERK1 was shown to bind chitin and trigger immune responses as a kind of "all-in-one" receptor. On the other hand, CEBiP seems to play a major role in the perception of chitin in rice, as the knockdown of CEBiP almost abolished the binding of a radio-labeled chitin oligosaccharide to the plasma membrane, whereas OsCERK1 was shown not to bind chitin (6,12). Liu …”
mentioning
confidence: 99%